POLICY FORMULATION OF CRIMINAL LAW ON ILLEGAL POSSESSION OF FIREARMS IN CRIMINAL LAW REFORM IN INDONESIA - Ermala, Candra; Jaelani, Agus; Mistari, Ari; Riyanto, Andri (Ann Publisher, 2025)
Abstract: Background. Firearm abuse is the most common case today. Aim. The flow of crime using the threat of violence or with firearms is indeed very disturbing to public security and order, causing concern in the community. Methods. This research uses normative juridical legal research, which has a descriptive nature, meaning it is based on laws and regulations closely related to the problem being researched, sourced from facts in society, and secondary literature or data. Results. Firearms for ordinary people are objects/tools used to attack or defend themselves, which, if fired, can cause serious injury or death, and one of the crimes that most disturbs the community is the crime involving the use of firearms. Conclusions. The current policy of criminal law formulation, especially regarding the current Illegal Firearms Possession Crime Formulation Policy, has many fundamental weaknesses, that it affect the level of effectiveness in the implementation of the eradication of the crime of Illegal Firearms Possession Involvement. Criminal law policy aimed at eradicating the crime of illegal firearm possession in the future should include the qualification of delicacy, as well as provide an understanding of juridical limitations regarding